2011
DOI: 10.1161/strokeaha.110.600783
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor I Serum Levels Influence Ischemic Stroke Outcome

Abstract: Background and Purpose— Insulin-like growth factor I (IGF-I) is neuroprotective in animal models of stroke. We investigated whether serum IGF-I levels in patients with acute ischemic stroke influence stroke severity and outcome. Methods— Concentrations of IGF-I and IGF binding protein 3 were measured in serum samples obtained within 6 hours after stroke onset from 255 patients who took part in the placebo arm of the United States and Canadian Lubeluzole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 17 publications
1
66
1
1
Order By: Relevance
“…The serum concentration of IGF-1 or the IGF-1/IGFBP-3 complex has been correlated with neurological recovery 19,39 due to IGF-1 anti-apoptotic and neuroprotective actions. 14 De Smedt et al 39 showed that individuals who had elevated levels of serum IGF-I or IGF-I/IGFBP-3 at 6 hours after a stroke were associated with better neurological recovery and functional outcome at 3 months, …”
Section: Discussionmentioning
confidence: 99%
“…The serum concentration of IGF-1 or the IGF-1/IGFBP-3 complex has been correlated with neurological recovery 19,39 due to IGF-1 anti-apoptotic and neuroprotective actions. 14 De Smedt et al 39 showed that individuals who had elevated levels of serum IGF-I or IGF-I/IGFBP-3 at 6 hours after a stroke were associated with better neurological recovery and functional outcome at 3 months, …”
Section: Discussionmentioning
confidence: 99%
“…99 High serum levels of insulin-like growth factor 1 after stroke are associated with neurological recovery and better functional outcome. 100,101 In experimental stroke, insulin-like growth factor 1 treatment improved motor recovery, paralleled by enhanced neovascularization and neurogenesis. 102,103 However, because of its inability to pass through blood-brain barrier, insulin-like growth factor 1 was administered intranasally starting 10 minutes after stroke induction 102 or by adeno-associated virus-mediated gene transfer 3 weeks before stroke.…”
Section: Growth Factorsmentioning
confidence: 99%
“…In a study of 255 stroke patients, higher IGF-1 levels or a higher IGF-1/IGFBP3 ratio was associated with better functional outcome at 3 months. Interestingly, baseline severity was not different between high and low IGF-1 groups, suggesting that IGF-1 modulates stroke sequelae and not the immediate phase (De Smedt et al, 2011). In a case cohort of older individuals in the Cardiovascular Health Study, neither IGF-1 nor IGFBP-1 predicted MI or stroke, but low IGFBP-3 levels were associated with higher levels of coronary events.…”
Section: Introductionmentioning
confidence: 98%